2014
DOI: 10.1017/jie.2014.17
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Secondary Education in the Northern Territory: Building for the Future

Abstract: This article reports on the findings of an Australian Research Council (ARC) funded research project, ‘Building the future for Indigenous students’, an investigation of the hopes and dreams for the future of over 1,000 secondary students, 733 of whom were Indigenous, living in very remote, remote, and urban locations in the Northern Territory. Using both quantitative and qualitative research tools, researchers sought to understand what motivated the students at school and how they studied — critical elements i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…In addition, there was aspiration to "move around" the various employment options as they "might get bored", which was shown to have historical precedent in the community (Senior, 2012, p. 378). Herbert et al, (2014), said that one of the major differences between the responses of very remote and less remote Aboriginal students in regards to their future was that "very remote students reported that they aspired to locally relevant work roles; for example, at the shop, the childcare centre, the health clinic, the school and through the CDEP scheme" (p. 92).…”
Section: Aspirations For the Futurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there was aspiration to "move around" the various employment options as they "might get bored", which was shown to have historical precedent in the community (Senior, 2012, p. 378). Herbert et al, (2014), said that one of the major differences between the responses of very remote and less remote Aboriginal students in regards to their future was that "very remote students reported that they aspired to locally relevant work roles; for example, at the shop, the childcare centre, the health clinic, the school and through the CDEP scheme" (p. 92).…”
Section: Aspirations For the Futurementioning
confidence: 99%
“…In addition, young First Nations people in remote areas of the NT have the view that the purpose of school or getting an education is to get a job in the future (Parkes, 2013, p. 31;Herbert et al, 2014). This is one of the pervading paradigms of the current education system in Australia and is based on Human Capital Theory (Guenther, Disbray & Osborne, 2014).…”
Section: Aspirations For the Futurementioning
confidence: 99%
“…The literature on factors impacting the participation and engagement in higher education of Indigenous students has largely focused on financial issues (e.g. Asmar et al, 2011;Hossain et al, 2008;Radloff & Coates, 2010), economic and sociocultural issues (Wilks & Wilson, 2012) and issues of remoteness (Herbert et al, 2014). Several studies (Andersen et al, 2008;Behrendt et al, 2012;Hossain et al, 2008;Trudgett, 2008Trudgett, , 2010Trudgett, , 2014) also suggest having a curriculum dominated by Western practices and epistemologies, lack of institutional support, lack of university readiness, lack of a research skill set, and issues in the student-supervisor relationships have affected Indigenous university and HDR students' participation, engagement and completion rates in Australian higher education.…”
Section: The Participation and Retention Of Indigenous Students In Au...mentioning
confidence: 99%
“…Moreover, educational disparities are much starker among high school students, particularly in remote Aboriginal communities (Herbert et al, 2014). School attendance rates drop steeply from fifth grade onwards; by tenth grade, the attendance rate in very remote areas is only 40 percent (He et al, 2018).…”
Section: B Heterogeneity By Gender School Level and School Attachmentmentioning
confidence: 99%